Huando: Land Reform and Law - Rubio Correa, Marcial (1973)
In the latter half of the 20th century, Peru initiated agrarian reform efforts to restructure land tenures, notably exemplified by the subdivision of the Huando estate. This process encountered multifaceted legal and political challenges. This paper conducts a comprehensive examination of the legal intricacies stemming from the Huando estate's subdivisions, with a specific emphasis on administrative complexities. Additionally, it scrutinizes the rulings of the agrarian court pertaining to parceling, aiming to elucidate procedural and administrative dimensions. By delving into these aspects, the study seeks to discern the legal underpinnings shaping judicial determinations.